Single-nucleus RNA sequencing reveals the specific molecular signatures of myeloid cells responding to brain injury after microglial replacement - Xiong, Xiao-Yi; Yuan, Haicheng; Mu, Ying; He, Yi; Xie, Fang; Feng, Xiao-Shuang; Xie, Jia-Xin; Pan, Xin-Ru; Wang, Yu-Fei; Gong, Jian; Zheng, Xiaoming; Wang, Peng-Fei (Frontiers in Immunology, 2025)
BackgroundMyeloid cells, such as resident microglia (MG), infiltrating monocytes (Mo), macrophages (MΦ), and CNS border-associated macrophages (BAM) in the brain, participate in aged brain injury. Aged microglial replacement is protective against brain injury in aged mice; however, whether/how the molecular changes in myeloid cells are affected by this replacement in injured brains remains unclear.MethodsAged microglia in mice were eliminated by PLX3397 for 21 consecutive days and repopulated following withdrawal for 21 days; then, intracerebral hemorrhage (ICH) models were constructed. Then, a single-nucleus transcriptomic analysis of acutely injured brains in aged mice with microglial replacement was performed.ResultsWe observed similarities but strong divergence in the composition and molecular change features of myeloid cells between the replacement (Rep) and control (Con) groups, indicating retention of the core transcriptome and development of differential genes in myeloid cells after microglial replacement in response to brain injury. Both MG and Mo/MΦ experience modification of immune responses after microglial repopulation, with more prominent changes in MG. Gene Ontology (GO) analysis showed that one term directly related to the “immune response” was shared between upregulated genes in Rep-MG and Rep-Mo/MΦ, while the other terms related to immune functions and other biofunctions were different between Rep-MG and Rep-Mo/MΦ, indicative of significantly different immune responses to brain injury between MG and MΦ. Furthermore, the trajectory analysis showed a significant transition from aged to young state in Rep-MG compared to only a modest youthful shift in Rep-Mo/MΦ, suggesting a rejuvenation process of aged microglia and macrophages toward young ones in response to brain injury after the treatment of microglial replacement.ConclusionOur data indicate that microglial replacement-induced changes in the molecular heterogeneity and state transition of myeloid cells may be neuroprotective against acute brain injury.